TEKANAN STRUKTURAL, PELUANG POLITIK, DAN SUKSES GERAKAN PETANI DI LAMPUNG - Hartoyo, Hartoyo (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This study was aimed at explaining one of the conflicts in Lampung Province who developed into a peasant movement. Interestingly, this peasant movement overran the land and agrarian policy influence to form a new village. Data were obtained from depth interviews and documentary studies. The results found that the structural pressures led to the accumulation of land conflicts crystallize into